Retention behaviors of different attachment systems: Precious versus non-precious, precision versus semi-precision - EVREN, BUKET; YILDIZ, COŞKUN; GÖZNELİ, RİFAT (JAPANESE SOC DENTAL MATERIALS DEVICES, 2013)
The aims of this study were to investigate the retention force changes of different attachment systems after 10,000 insertion-separation cycles and the difference in retention force between precious and non-precious materials of the same attachment system. Four types of attachments (Ball, Rod, M3 stud, and AP-Piccolino), produced using both precious and non-precious metal alloys, were tested (n=6). Data were analyzed using analysis of variance (ANOVA), Tukey's multiple comparison test, and t-test at a significance level of p <= 0.05. Retention forces of all attachment types were significantly decreased after 10,000 insertion-separation cycles (p <= 0.05). Rod and M3 attachment systems showed an initial increase in retention force, then an eventual decrease. At the end of the test, precious types of M3 and AP-Piccolino attachments had significantly higher retention force values than their non-precious ones (p <= 0.05). Friction between non-precious attachment parts resulted in a higher retention loss than precious metal alloys.
Keywords: Attachment; Precious; Precision; Retention force; PREFABRICATED ATTACHMENTS; WEAR